Anselm Heinrich. Theatre in Europe Under the German Occupation. Routledge, 2018. - Scott G. Williams (Studies in 20th & 21st Century Literature, 2020)
Review of Anselm Heinrich. Theatre in Europe Under the German Occupation. Routledge, 2018. 274 pp.
Keywords: theatre history; German history; interdisciplinary studies